Multimedia Assisted Analogy: Learning Approach to Developing Mathematical Representation Skills - Dwirahayu, Gelar; Tantri K., Dyah; Afidah, Afidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to examine the application of mathematics learning using a multimedia-assisted analogy approach in developing mathematical representation. The sample used was grade 7 students of two classes, totaling 44 students. The research method used was a quasi-experimental design with randomized posttest only. Two classes were randomly selected as samples, namely class VII-1 as the experimental class and class VII-3 as the control class. The analysis was performed using the t-test at Î± = 5%, obtained t-count = 4.205> t-table = 2.018. The results indicate that the mathematical representation ability of students whose learning uses the analogy approach is significantly higher than students whose learning uses a conventional approach or in other words, the multimedia-assisted analogy approach can be used as alternative learning in developing student representation abilities especially in algebraic material.